2014
DOI: 10.1016/j.jpsychores.2013.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Does attachment anxiety increase vulnerability to headache?

Abstract: Objective. To determine whether adult insecure attachment dimensions were associated with headache or sensitivity to pain before, during or after stressful mental arithmetic in an episodic migraine and tension-type headache (T-TH) sample.Background. The relationship styles of attachment insecurity, both anxious and avoidant,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 93 publications
(91 reference statements)
0
22
0
1
Order By: Relevance
“…Similarly to MS, also headache appears to be closely correlated with depressive symptoms, particularly when disease becomes chronic causing feelings of inadequacy, negative thinking, diminished interest for environment and relationships, affecting patients’ quality of life – QoL (Blomkvist et al, 2002; Manack et al, 2011). In the last decade, however, it has been suggested that depressive and anxious features, as well as other psychological aspects, may be a distinctive characteristic of this population of patients, instead of a consequence of experimenting chronic pain (Mongini et al, 2000; Torelli et al, 2008; Berry and Drummond, 2014; Bottiroli et al, 2016; Muñoz et al, 2016). In ALS population, by contrast, Major Depressive Disorder (MDD) seems to be an uncommon result, with a prevalence similar to that of the adult general population (Norris et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to MS, also headache appears to be closely correlated with depressive symptoms, particularly when disease becomes chronic causing feelings of inadequacy, negative thinking, diminished interest for environment and relationships, affecting patients’ quality of life – QoL (Blomkvist et al, 2002; Manack et al, 2011). In the last decade, however, it has been suggested that depressive and anxious features, as well as other psychological aspects, may be a distinctive characteristic of this population of patients, instead of a consequence of experimenting chronic pain (Mongini et al, 2000; Torelli et al, 2008; Berry and Drummond, 2014; Bottiroli et al, 2016; Muñoz et al, 2016). In ALS population, by contrast, Major Depressive Disorder (MDD) seems to be an uncommon result, with a prevalence similar to that of the adult general population (Norris et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with migraine have been described as having particular difficulties in recognition of their own emotions, showing high levels of anxiety and frequent concerns about their health (Yucel et al, 2002; Norton and Asmundson, 2004), suggesting such features as distinctive patients’ characteristics (Torelli et al, 2008; Berry and Drummond, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Berry and Drummond [20] speculated that anxiously attached individuals may express greater pain or may show a stronger attentional bias toward painful sensations than securely attached ones increasing the likelihood of developing headache per se. Our results are in keeping with authors suggesting that an avoidant attachment may represent a risk factor for psychopathology in patients with migraine [21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a large portion of the literature investigating attachment styles and pain has drawn conclusions based on patients with headaches or migraines (e.g., [15,30,31,32]) and functional abdominal pain (e.g., [33,34]). However, if acute physical threats are likely to activate attachment-based behaviors [16], it seems conceivable that attachment behavior patterns may contribute to an acute pain problem which has resulted from an injury or surgery transitioning into a chronic pain problem.…”
Section: Attachment Framework and Vulnerability And Maintenance Ofmentioning
confidence: 99%